If it's not what You are looking for type in the equation solver your own equation and let us solve it.
90-9x-27=9x+9
We move all terms to the left:
90-9x-27-(9x+9)=0
We add all the numbers together, and all the variables
-9x-(9x+9)+63=0
We get rid of parentheses
-9x-9x-9+63=0
We add all the numbers together, and all the variables
-18x+54=0
We move all terms containing x to the left, all other terms to the right
-18x=-54
x=-54/-18
x=+3
| 3=h/5-6=-7 | | 5+2a-9+4a=14 | | .2r+7–r= | | a=3;a+10= | | 4+3x=5x-12 | | 5m-6=18 | | 5x8=7x-32 | | 4x-1x=19+14 | | 4x-1x=19+4 | | x+14.5=63.3 | | 6w-3w=29-8 | | 99+y=194 | | X/6+y/70=250 | | -1=x²-2x | | 56=3m+2(m+3) | | 5-3y=11-4y | | 2x*2=3x+104 | | (1/15)-(7x)/5=21 | | 31=2g-4 | | 8s+2+s=58 | | 7x÷8-1÷4=4x÷5+11÷4 | | x6/3=1 | | 9x-3+4x=5 | | x+7=103 | | x-30.8=41.1 | | 7(x+2)=5(3x-1) | | x-53=23 | | 100=25c | | 4+5x=7+9 | | 22=a-5 | | -7-2x=-27 | | 21=4m+6 |